Can Women Save Japan? - Steinberg, Chad.; Nakane, Masato (Washington, D.C. : International Monetary Fund, 2017)
Japan's potential growth rate is steadily falling with the aging of its population. This paper explores the extent to which raising female labor participation can help slow this trend. Using a cross-country database we find that smaller families, higher female education, and lower marriage rates are associated with much of the rise in women's aggregate participation rates within countries over time, but that policies are likely increasingly important for explaining differences across countries. Raising female participation could provide an important boost to growth, but women face two hurdles in participating in the workforce in Japan. First, few working women start out in career-track positions, and second, many women drop out of the workforce following childbirth. To increase women's attachment to work Japan should consider policies to reduce the gender gap in career positions and to provide better support for working mothers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet